ANALISIS IMPLEMENTASI MODEL DISCOVERY LEARNING DALAM PEMBELAJARAN IPA DI MASA PANDEMI COVID-19 - Anita Siska Alfiana; Erman Erman; Dhita Ayu Permata Sari (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
The purpose of this study was to find out how the science teacher at MTs Negeri 1 Sidoarjo used discovery learning, constraints and students’ inductive and deductive thinking skills in the implementation of online discovery learning. This research used case study method. The subjects in this study were one science teacher and 15 students from class IX-C MTs Negeri 1 Sidoarjo, which used discovery learning during online learning. This study was focused on 3 topics: plant breeding, magnetism, and food biotechnology. Instruments were used in this study were guidelines for teacher and student interview, checklist instruments for learning plans, student response questionnaires and student inductive and deductive questions. Document analysis techniques, semi-structured interviews, surveys, and tests for students’ inductive and deductive thinking skills were used in this study, and data were analyzed qualitatively and quantitatively. The result of this study indicates that: (1) The learning plans made by the teacher on three topics reached a percentage of 100% because all stages of discovery learning have been included in lesson plans; (2) The implementation of discovery learning on three topics studied reached a percentage 61%, which indicates that it has not been implemented optimally because there were discovery learning stages that were not carried out during learning, such as problem statement, verification, and generalization stages; (3) The students’ inductive thinking test result reached 64%, while deductive thinking test result reached 72%. Because lack test results were that application of the discovery learning has not been optimal which could affect the quality of student learning.